Management of a Periodontal Pocket Using a Removable Orthodontic Appliance and Nonsurgical Periodontal Therapy - Serhat Köseoğlu; Ahmet Fidancıoğlu; Mehmet Sağlam; Levent Savran (Case Reports in Dentistry)
Purpose. As documented in the literature, bony defects can be managed by an orthodontic approach. Methods. This case report describes the treatment of a bony defect caused by orthodontic malposition through phase I periodontal therapy and a simple removable orthodontic appliance used for the first time in a 20-year-old girl. Results. The periodontal pocket was reduced from 8 mm to 3 mm shortly after treatment. Conclusion. This case report concludes that orthodontic therapy can be used successfully in treatment of bony defects caused by mesially tilted molars.